TARAS SHEVCHENKO IN THE LIGHT OF «NON FICTION» LITERATURE - Ільків, А. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the aesthetic constituent of T. Shevchenko’s epistles. Problems of national identity in the poet’s early letter through contradistinction of “my” and “other’s” worlds.